Some Classical Sequence Spaces and their Topological Structures - Pahari, Narayan Prasad (Journal of Advanced College of Engineering and Management, 2016)
The aim of this paper is to study some of the basic scalar and vector valued sequence spaces. We also study the topological structures of some of the basic sequence spaces when topologized through a norm or a paranorm. Journal of Advanced College of Engineering and Management, Vol. 1, 2015, PP. 59-65